CHALLENGES TO WOMEN’S HEALTHCARE RIGHTS: INTERNATIONAL AND NATIONAL DIMENSIONS - Belousova, Anastasia; Belousova, Alexander; Kuznetsova, Оlga; Ilyashevich, Marianna; Koupchina, Ekaterina (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to consider the current state of affairs and future prospects in terms of women’s health care protection. To reach the above goal the research provides historical analysis of legislation framework development regarding the women’s health protection, study women’s health concept within current international legislation, maps global challengers regarding the women health care. The research rested on qualitative principles of analysis and used general scientific methods: analysis, logical method, generalization, as well as a special and a comparative legal method. The research materials included international white papers with regard to women’s health. The article provides analysis of states commitments to ensure women’s rights to health care as well as examine the practice of individual states in the particular field. The study involves statistics on women's reproductive health regarding the protection of maternal health, maternal mortality and the provision of qualified medical care.